2014
DOI: 10.5115/acb.2014.47.2.117
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the effect of high cholesterol diet on the hippocampal CA1 area of adult and aged rats

Abstract: Dementia is one of the most important problems nowadays. Aging is associated with learning and memory impairments. Diet rich in cholesterol has been shown to be detrimental to cognitive performance. This work was carried out to compare the effect of high cholesterol diet on the hippocampus of adult and aged male albino rats. Twenty adult and twenty aged male rats were used in this study. According to age, the rats were randomly subdivided into balanced and high cholesterol diet fed groups. The diet was 15 g/ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…29 Finally, the present study tries to direct public attention to low cholesterol intake in the food to maintain a healthy life style. 30 In the limitations of this study, the study was performed only for 4 weeks. No dose oscillation was performed.…”
Section: Discussionmentioning
confidence: 97%
“…29 Finally, the present study tries to direct public attention to low cholesterol intake in the food to maintain a healthy life style. 30 In the limitations of this study, the study was performed only for 4 weeks. No dose oscillation was performed.…”
Section: Discussionmentioning
confidence: 97%
“…[35] What is more, elevated dietary cholesterol has been reported to increase Aβ accumulation or deposition in numerous animal models. [36][37][38][39] We have verified that dietary cholesterol increased Aβ production and accumulation in brain, which resulted in learning and memory impairment significantly. Since cholesterol levels influence the production and deposition of the pathogenic Aβ, cholesterol transport and homeostasis are thus closely linked to multiple aspects of Aβ biology.…”
Section: Discussionmentioning
confidence: 98%
“…Decreased PPAR expression in the adipose tissue (20) of hypercholesterolemic mice was related to a modified expression of the genes that explain decreased insulin sensitivity and glucose transport, elevated hypertriglyceridemia, inflammation, and increased oxidative stress. The association of insulin sensitivity (21), glucose transport (22), elevated hypertriglyceridemia (23), inflammation (17,24), and increased oxidative stress (25) with AD has already been established. In the current study, measurement of brain weight in the test group showed no change in brain wet weight, which supported findings in another study (11).…”
Section: Discussionmentioning
confidence: 99%